Formation and Maturation of the Native Cerebral Collateral Circulation - Chalothorn, Dan (2010)
The native (pre-existing) collateral circulation minimizes tissue injury if obstructive vascular disease develops. Evidence suggests large differences in collateral extent exist among healthy individuals, presumably from as-yet unknown genetic and/or environmental factors. Little is known regarding when or how native collaterals form—information needed to identify these factors. We examined collateral development between the middle and anterior cerebral artery trees in BALB/c and C57BL/6 mouse embryos—strains with marked differences in adult collateral density and diameter (85% fewer, 50% smaller in BALB/c). The circulation was dilated, fixed and stained. By E15.5, a “primary collateral plexus” was beginning to form in both strains. By E18.5, plexus vessel number peaked, but was 60% less and diameter smaller in BALB/c (P<0.001). Earlier time-points were examined to determine if these differences correlated with differences in patterning of the general circulation. At ~E9.0, the primary capillary plexus was similar between strains, but by E12.5 branching was less and diameter larger in BALB/c (P<0.05). Between E12.5–E18.5—during pial artery tree development—small differences in tree size, branch number and distance between branches did not correlate with the large difference in collaterogenesis. Pruning of nascent collaterals between P1–P21 was comparable in both strains, yielding the adult density, but diameter and tortuosity increased less in BALB/c. Pericyte recruitment to nascent collaterals was comparable, despite lower VEGF-A and PDGF-B expression in BALB/c mice. These findings demonstrate that collaterals form late during vascular development and undergo postnatal maturation, and that differences in genetic background have dramatic effects on these processes.